PUBLIC VALUE BASED E-GOVERNMENT MATURITY MODEL: A LITERATURE REVIEW - Titisari Ramadhane; Luthfi Ramadani; Lukman Abdurrahman (JIKO (Jurnal Informatika dan Komputer), 2023)
Public value is a means for evaluating the effectiveness and efficiency of public services and an E-Government maturity model that controls the process for developing and maintaining E-Government services. Previous studies have analyzed and discussed public values, maturity models. Therefore, it is necessary to examine what public values should be present in E-Government based on the E-Government maturity model. This study aims to develop public values based on the E-Government maturity model and fill the gaps in the literature research by categorizing the dimensions of public values and the existing E-Government maturity models. This research method uses a systematic literature review (PRISMA). A total of 60 articles were selected, classified, and analyzed according to the criteria of public value and the specified dimensions of the E-Government maturity model. From the results of the literature review analysis, there are similarities between the dimensions of public value and the dimensions of the E-Government maturity model so that some of these dimensions can be combined to form a new public value dimension based on considerations from the dimensions of the E-Government maturity model, namely (1). Public Services in Government (2). Dimensions of Administration in Government, (3). Open Government (OG), (4). Ethical Behavior and Professionalism, (5). Trust and Confidence in Government (6). Social Value in Government. This study aims to strengthen public values based on the E-Government maturity model. It is hoped that implementing sustainable E-Government services will become easier by analyzing public values based on the E-Government maturity model.